Measuring Fiscal Decentralization : Exploring the IMF's Databases. (IMF Working Papers; Working Paper, 2011)
Conventional wisdom postulates that there are benefits from decentralizing government finances but there is little empirical evidence about actual country practices. This paper presents data on fiscal decentralization for about 80 countries over a period of about 20 years (1990-2008) from the IMF's Government Finance Statistics Yearbook (GFSY), the only global database with fiscal data for several levels of government. The data show that in many countries, revenue collection remains relatively more centralized than expenditures and that employment tends to be concentrated in lower levels of government. Except for transition economies, the levels of decentralization are relatively stable over the time period. The findings are shown by degree of economic development, constitutional power arrangements, and geographic area, broadly confirming key factors identified in the literature as determining the extent of fiscal decentralization.